Combustion and engine roughness of water − jojoba biodiesel emulsions in diesel engine - Ihab Ayad; Mohamed Y.E. Selim; Mamdouh T. Ghannam (Energy Conversion and Management: X)
This study investigates for the first time the effects of using Jojoba biodiesel-water emulsion in a diesel engine combustion, engine performance, exhaust emissions, block vibration and noise. The engine analysis was conducted using a single-cylinder diesel engine equipped with a pressure sensor in the combustion chamber, an accelerometer for vibration measurement, microphone condenser probe for noise, an external flow meter to measure the fuel flow rate, and an orifice meter to measure the air flow rate. The engine speed varied from 1600 to 2100 rev/min, and the fuel pump rack position was adjusted to middle position to control the engine power output. The fuel used was Jojoba biodiesel − water emulsion at different water ratios (0%, 5%, 10%, and 15%) and compared to pure diesel. The data recorded continuously over time included cylinder combustion pressure, sound pressure level (external noise), block vibration smoke opacity, and exhaust gases. The results showed that the use of Jojoba biodiesel-water emulsion led to a reduction in NOx and HC emissions compared to jojoba biodiesel, and a reduction in exhaust gas temperature. Brake power and maximum cylinder pressure were not significantly affected by adding water the jojoba biodiesel. The study provides valuable insights into the potential of Jojoba biodiesel-water emulsion as an alternative engine fuel.